A survey of ground beetles (Coleoptera: Carabidae) in Ahuriri Scenic Reserve, Banks Peninsula, and comparisons with a previous survey performed 30 years earlier. Issue 4 (2nd October 2019) - Bowie, Mike H.; Shields, Morgan W.; He, Shuqi; Ross, James G.; Cruickshank, Rob H.; Hodge, Simon
ABSTRACT: Carabidae (Coleoptera) are commonly used as indicators of ecosystem health due to their high diversity, conservation value and relative ease of identification. Carabids were monitored at Ahuriri Scenic Reserve, Port Hills, Canterbury, from August 2007 to September 2008 using pitfall traps. Carabid captures, species richness and distribution across the reserve were compared with those found in a similar study in 1977–1978. Monthly carabid captures were highly correlated with average temperature in both studies. There was little evidence of carabids responding to habitat factors, such as leaf litter depth, pH or ground cover. However, Megadromus antarcticus was positively associated with canopy openness and ground cover, whereas Holcaspis angustula was more abundant where canopy cover was extensive and there was a relatively high incidence of bare rock. Thirteen species of carabid were recorded in 1977–1978, of which six were absent, four had decreased, one was stable and two species increased in abundance from collections made in 2007–2008. The loss of one Banks Peninsula and five New Zealand endemic beetle species from this reserve is of concern, and future work should aim to gain more detailed information on the habitat requirements of these species to assist conservation management strategies.